Basic education in Mexico: A comparative analysis of the educational models of 2011 and 2016 - Cristina Araceli Cantú Leal; Alex Iván Arévalo Salinas; Reyna Lizeth Vázquez Gutierréz (Arizona State University, 2018)
This document makes a comparative study of two educational reforms in México, the basic education (RIEB) of 2011 and the educational model 2016, which will become active in 2018, when its new plan and curriculum will implement. The objective is to analyze the similarities and differences of these educational standards, both at the structure level and in relation to their main characteristics. For this, 25 criteria and parameters of analysis will be defined, starting from a procedure of sequential character study. This qualitative research is complemented by bibliographic sources concerning on quality education in Mexico, within the reform process that has experienced the sector since the early 90´s.The results reflect that of 25 criteria developed for this research, these normative differ in 6.